A cation–π interaction confined graphene oxide membrane for separation of light paraffins and olefins. Issue 35 (13th April 2023) - Chen, Huiling; Guo, Bing; Gong, Dian; Fan, Jingrui; Li, Zhi; Wang, Chuhao; Wang, Lu; Yu, Chengbing; Wang, Chenyu; Zeng, Gaofeng
Abstract : Selective permeation of light paraffins over olefins, e.g., a propane to propylene ideal selectivity of 1817, is observed from a modified GO membrane, which is intercalated with metal ions. Abstract : A supported graphene oxide membrane is endowed with selective function for olefins by a cation intercalation method. The metal-cation fixed GO membrane exhibits a high propane to propylene ideal selectivity of 1817 for single gas and a separation factor of 7.1 for binary mixtures with fast gas permeance in the order of 10 −7 mol m −2 s −1 Pa −1 and reliable permeation stability.